Profil Mikrobiologis dan Deteksi Mastitis dengan California Mastitis Test di Peternakan Sapi Perah Novisiat Claretian Benlutu - Yosef K. Tamur (JAS, 2020)
This research has taken place at Claretian Novitiate of Benlutu dairy cattle, Batu Putih district, TTS regency for a month. The research was conducted in two periods, the test of CMT and laboratory analyzes. The aim of this study are to identify the profile microbiological infected dairy milk suffering of mastitis by using CMT. In conducting the researcher, this research used four lactation dairy cattle as samples. The result of the study showed that the Claretian Novitiate of Benlutu dairy cattle infected by subclinical mastitis so it needs intervention to prefent mastitis. The quality of the milk is good based on the quality of bacterial and the reducting time has been approved of SNI.